Réponses

2012-12-28T14:19:10+01:00
Meilleure réponse !
2012-12-28T15:00:54+01:00

voici les réponses .

 

5x-7= 3x+9        7-(3+x)=5x         2(5-3x) =7       6(4-5x) = 5(10+4x)

5x-3x=9+7         7-3-x =5x            10-6x = 7         24-30x = 50+20x

2x=16                 4-x =5x                10-7 =6x          -30x-20x = 50-24

x=16/2                4 =6x                   3 = 6x               -50x = 26

x=8                      x = 4/6                 x = 3/6              x = -26/50

                                                                                   x = -13/25